An Analysis of Subtitling Strategies in the Indonesian Film “Rumah Dara” - Meli Budiarti (Passage, 2017)
This research attempts to explore kinds of subtitling strategies, the most-frequently strategies found, and the contribution of the most-frequently strategies found in an Indonesian film Rumah Dara. In conducting the analysis, the research uses a theoretical framework of subtitling strategy proposed by Gotlieb (1994). In terms of its approach, this research belongs to descriptive approach. The data are in the forms of transcripts of the film Rumah Dara. The transcripts consist of 651 dialogues. This research shows that the most-frequently found strategy is transfer (42.55%). It is then followed by imitation (14.44%), condensation (11.21%), and paraphrase (10.91%). Therefore, the results of this research are expected to contribute to the improvement of translational quality in Indonesian films. In addition, it enriches the study of subtitling analysis in Indonesian thriller film.Keywords: Translation, Audiovisual Translation (AVT), Subtitling, Subtitle Strategies